COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN KERAJINAN BLANGKON DI KECAMATAN SERENGAN KOTA SURAKARTA - Lukito & Aris Tri Haryanto (Master of Public Administration, Universitas Slamet Riyadi, 2016)
This research aimed to study factors succeeding as well as inhibatingcollaborative governance in developing blankon handicraft. The researchemployed seven indicators to measure the degree of success and of failuresaffecting collaborative government. 1) Network structure; 2) Comitment tocommon purpose; 3) Trust among the participants; 4) Access to authority; 5)Distributive accountability/responsibility; 6) Information sharing; and 7) Accessto resource. Qualitative research approach was used in this study. Researchresult showed that the implementation of collaborative governance indeveloping blankon handicraft was not optimally obtained due to: a)Collaborative government was not decided under the letter of memorandum ofunderstanding. b) In implementing collaborative governance the commitment ofauthority depended on each stakeholder. Thus, there was no clear networkstructure. The seven indicators employed for analysing collaborativegovernance research result showed that: 1) Network structure had alreadyworked, however, it did not optimally work due to that there was no decisionunder the memorandum of understanding. 2) Commitment to common purposeamong the stakeholders had already agreed among the stakeholers, however, itwas only coordinative in nature. That is why, the common commitment can bedenied; 3) Trust among the participant. There was no full trust among theparticipants; they are duobtful. 4) Access to authority done according theexisting authority and according to each task; 5) Distributive accountability orability to respond did not happen among related institutions, but it dependedupon each institution and each did not influence among others; 6) informationsharing has already worked; information was easily accessable; 7) Access toresource only worked for the governmental and corporate instituions since theyhad enough resources, but on the other hand the stakeholder, i.e. thehandicrafters and their assiciations did not have enough resources.Key words: Collaborative governance, Network structure; Commitment to commonpurpose; Trust among the participants; Governance; Access to authority;Distributive accountability/responsibility; Information sharing; Access toresource.